Recent advances in therapeutic use of transforming growth factor-beta inhibitors in cancer and fibrosis - Jing, Hanhui; Gao, Yan; Jing, Linyuan; Yang, Hanyu; Liu, Shanglong (Frontiers in Oncology, 2025)
Transforming growth factor-beta (TGF-β) has long been known to be associated with early embryonic development and organogenesis, immune supervision, and tissue repair and homeostasis in adults. TGF-β has complex roles in fibrosis and cancer that may be opposing at different stages of these diseases. Under pathological conditions, overexpression of TGF-β causes epithelial–mesenchymal transition, deposition of extracellular matrix, and formation of cancer-associated fibroblasts, leading to fibrotic disease or cancer. Fibroblasts, epithelial cells, and immune cells are the most common targets of TGF-β, while fibrosis and cancer are the most common TGF-β-associated diseases. Given the critical role of TGF-β and its downstream molecules in fibrosis and progression of cancer, therapies targeting TGF-β signaling appear to be a promising strategy. Preclinical and clinical studies have investigated therapies targeting TGF-β, including antisense oligonucleotides, monoclonal antibodies, and ligand traps. However, development of targeted TGF-β therapy has been hindered by systemic cytotoxicity. This review discusses the molecular mechanisms of TGF-β signaling and highlights targeted TGF-β therapy for cancer and fibrosis as a therapeutic strategy for related diseases.